Effects of Propofol on Electrical Synaptic Strength in Coupling Reticular Thalamic GABAergic Parvalbumin-Expressing Neurons - Zhang, Yu; Liu, Chengxi; Zhang, Lin; Zhou, Wenjing; Yu, Shouyang; Yi, Rulan; Luo, Dan; Fu, Xiaoyun (Frontiers in Neuroscience, 2020)
Electrical synapses between neurons exhibit a high degree of plasticity, which makes critical contributions to neuronal communication. The GABAergic parvalbumin-expressing (PV+) neurons in the thalamic reticular nucleus (TRN) interact with each other through electrical and chemical synapses. Plasticity of electrical synaptic transmission in TRN plays a key role in regulating thalamocortical and corticothalamic circuits and even the formation of consciousness. We here examined the effects of propofol, a commonly-used general anesthetic agent, on the strength of electrical synapses between TRN PV+ neurons by fluorescence-guided patch-clamp recording and pharmacological methods. Results show that 100 μM propofol reduced the electrical synaptic strength between TRN PV+ neurons. Notably, the propofol-induced depression of electrical synaptic strength between TRN PV+ neurons was diminished by saclofen (10 µM, antagonist of GABAB receptors), but not blocked by gabazine (10 µM, antagonist of GABAA receptors). Application of baclofen (10 µM, agonist of GABAB receptors), similar to propofol, also reduced the electrical synaptic strength between TRN PV+ neurons. Moreover, the propofol-induced depression of electrical synaptic strength between TRN PV+ neurons was abolished by 9-CPA (100 μM, specific adenylyl cyclase inhibitor), and by KT5720 (1 μM, selective inhibitor of PKA). Our findings indicate that propofol acts on metabotropic GABAB receptors, resulting in a depression of electrical synaptic transmission of coupled TRN PV+ neurons, which is mediated by the adenylyl cyclase-cAMP-PKA signaling pathway. Our findings also imply that propofol may change the thalamocortical communication via inducing depression of electrical synaptic strength in the TRN.